(untitled) (Ogigia. Revista Electrónica de Estudios Hispánicos, 2024)
Among the successful educational actions that characterize a school with a learning community is the development of dialogic literary gatherings (DLGs) a practice that seeks to promote egalitarian dialogue between students and teachers to reflect on and value the cultural heritage of literary classics’ books. The present study aims to understand the teaching components that define this practice, through the teachers’ work. Following a qualitative ethnographic methodology, semi-structured interviews and a categorical analysis were applied after the participant observation of the work of two female teachers and a male teacher belonging to the same center, located in one of the most vulnerable areas of Granada, Spain, was observed. The results, organized in three thematic cores, show that teaching performances in the DLGs are conditioned by multiple factors. Among the most outstanding are the sociocultural context of the students, the meaning that teachers allocate to reading in school and the tensions they experience when working exclusively with literary classics. The conclusions make visible a relationship of dialogue and rupture between teaching and theoretical knowledge, together with the need to rethink reading itineraries that broaden reading experiences and cultural references.